A necrópole do Olival do Senhor dos Mártires (Alcácer do Sal). Novos elementos para o seu estudo: nota introdutória e organização de João Luís Cardoso - Paixão, António Manuel Cavaleiro (Estudos Arqueológicos de Oeiras, 2014)
In this article we present a selection of the most relevant data that A. M. Cavaleiro Paixão presented in 1970 in his graduate thesis he defended at Faculdade de Letras de Lisboa (Lisbon Faculty of Letters) about his archaeological fieldwork at the Iron Age necropolis of Olival do Senhor dos Mártires. This text was never published and 45 years later the important scientific interest of these excavations and its results remains and is even higher, due to the fact that in the last decades there has been an increasing knowledge of the Iron Age necropolis in southern Iberian Peninsula. Although the necropolis area excavated between 1966 and 1968 was small, the importance of the identified incineration graves and the recovered archaeological remains, carefully registered and characterized give to this work a major importance to the study of Iron Age, both in the Portuguese territory, as in southern Iberian Peninsula. This necropolis was first excavated during late 19th century and can be dated from the 7th to the 4th century BC, with influences from hinterland and Mediterranean as Cavaleiro Paixão already mentioned in his graduate thesis.